Detection avoidance and mis/unclassified, unsolved homicides in Australia. Issue 2 (18th December 2019) - Ferguson, Claire; McKinley, Amber
Abstract : Purpose: The purpose of this paper is to begin to explore whether and how the use of detection avoidance (DA) by offenders leads to a so called "dark figure" of unsolved homicides that have been mis/unclassified. Design/methodology/approach: Australian Coronial data and inquest findings are used to examine how DA impacts on determining homicide, and cases remaining unsolved. Findings: Results show DA behaviours perpetrated by offenders may be catalysed by other challenges, and may lead to homicides being mis/unclassified and unsolved. Findings indicate there is a small dark figure of mis/unclassified homicides which eventually become known and investigated as homicides in Australia. The number of unsolved homicides may be greater than official data reveals, due to some cases remaining mis/unclassified. Research limitations/implications: Results are likely to underestimate the prevalence of mis/unclassified homicides due to the invisibility of cases and the difficulty establishing rules to include suspected but unproven homicides. The variable nature and impact of DA behaviours also limits results, along with jurisdictional differences in Coronial data. Practical implications: This discussion explains DA behaviours impact on determining and investigating homicide and the necessity of future research. Originality/value: Mis/unclassified homicides as unsolved homicides have not been discussed previously. This discussion is the first to conceptualise mis/unclassified homicides as a dark figure of unsolved cases, and the first to attempt to gauge the problem.